Identification of critical residues at the C-terminal tip of ACKR4 regulating chemokine internalization and βarrestin involvement - Oliver J. Gerken; Nicola Catone; Daniel F. Legler (Cell Communication and Signaling)
Abstract Background Atypical chemokine receptors (ACKRs) play an important role in regulating the availability of chemokines and are responsible for the formation of chemokine gradients required for the directed migration of immune cells in health and disease. ACKR4 shapes gradients of the chemokines CCL19 and CCL21, which are essential for guiding leukocyte homing to lymphoid organs where they initiate an adaptive immune response against invading pathogens. How ACKRs internalize and scavenge chemokines on the molecular level remains poorly understood. Current state-of the art methods to study βarrestin recruitment, signaling and trafficking of ACKRs - and G-protein-coupled receptors in general - rely heavily on C-terminally tagged receptors with unknown consequences for receptor functions. Methods Fluorescently labelled CCL19 was used to quantify chemokine internalization by native and tagged receptors as assessed by flow cytometry and live cell confocal microscopy. Steady-state interaction and chemokine-driven recruitment of βarrestins was determined by NanoBiT bystander assays. βarrestin-dependency for CCL19 internalization was determined in wild-type versus βarrestin1/2-double deficient cell lines. Statistical significance was determined by unpaired t-test or one-way ANOVA with Dunnett’s or Tukey’s multiple comparison tests. Results Addition of a C-terminal tag selectively affected the function of ACKR4, but not other ACKRs. Fusing a short peptide tag or a fluorescent protein to ACKR4 significantly augmented its ability to internalize its cognate ligand CCL19. In comparison to native ACKR4, its C-terminal tagging provoked an elevated pre-association of βarrestins with the plasma membrane, yet a reduction in chemokine-driven βarrestin recruitment. Furthermore, the addition of a C-terminal tag led to a shift from a βarrestin-dependent towards a βarrestin-independent endocytosis pathway. Similar results on chemokine uptake and on βarrestin-dependency were obtained with ACKR4 variants, in which a putative class II PDZ-binding domain located at the C-terminal tip of the receptor was mutated. Conclusion This study identifies that the integrity of the C-terminus of ACKR4 is critical for receptor function. The addition of a C-terminal tag to ACKR4 enhances chemokine uptake and alters the involvement of βarrestins in receptor trafficking.